2016
DOI: 10.1016/j.elspec.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of rare earth hexaborides using high resolution angle-resolved photoemission

Abstract: Strong electron correlations in rare earth hexaborides can give rise to a variety of interesting phenomena like ferromagnetism, Kondo hybridization, mixed valence, superconductivity and possibly topological characteristics. The theoretical prediction of topological properties in SmB6 and YbB6, has rekindled the scientific interest in the rare earth hexaborides, and high-resolution ARPES has been playing a major role in the debate. The electronic band structure of the hexaborides contains the key to understand … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 68 publications
(158 reference statements)
8
21
0
Order By: Relevance
“…This Fermi surface agrees with previous measurements for CeB 6 (refs 27 , 28 , 29 , 30 ). The ellipsoids are typical for the hexaborides in general 28 29 . Their orbital character is composed of extended Ce 5 d states with admixtures of localized Ce 4 f near the Fermi energy ( E F ; ref.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This Fermi surface agrees with previous measurements for CeB 6 (refs 27 , 28 , 29 , 30 ). The ellipsoids are typical for the hexaborides in general 28 29 . Their orbital character is composed of extended Ce 5 d states with admixtures of localized Ce 4 f near the Fermi energy ( E F ; ref.…”
Section: Resultssupporting
confidence: 92%
“…The electronic structure derived here by soft X-ray photoemission from various cleavage planes is consistent with previous low photon energy studies from the (100) plane 28 29 . Neupane et al reported a strong k -dependent renormalization around the Γ point concluded from the deviation of the experimental data and the bandstructure calculation in this region and enhanced quasiparticle intensity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As discussed below, this small peak is most likely related to the indirect tunneling into the localized Γ (2) 8 states. Compared to delocalized f -states, such localized f -states may give rise to only small anomalies in spectroscopy measurements [43].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the observation of a gap opening at the Fermi level by spectroscopic measurements, transport experiments show signs of residual conductivity [4]. The origin of this residual conductivity has puzzled the scientific community until the recent discovery of low-temperature metallic surface states [5], of potential, albeit debated, topological character [6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%